Influence of Exogenous Ascorbic Acid Levels on Growth and Physiological Responses of Wheat (Triticum aestivum) Exposed to Drought Stress - Iftikhar, Hadaya; Arshad, Ayesha; Tamreen, Yamna; Shahid, Saba; Firdous, Malika; Siddiqui, Iqra; Fatima, Sara; Fatima, Rameen; Fatima, Huzeera; Ali, Qurban (Indus Journal of Bioscience Research, 2025)
Drought stress is a major environmental constraint that significantly threatens wheat (Triticum aestivum L.) production, particularly in regions like Pakistan, where wheat yields are relatively low. Water scarcity adversely affects plant growth and physiology, leading to decreased productivity. To mitigate these effects, various strategies have been explored, including the application of exogenous plant growth stimulants such as ascorbic acid (AsA). AsA is known to enhance plant tolerance against abiotic stresses by improving biochemical and physiological attributes. Despite its potential benefits, limited research has been conducted on the role of AsA in enhancing drought tolerance in wheat. There is a need for further investigation to determine the most effective concentration of AsA for improving wheat growth under water-limited conditions. In this study, a completely randomized design (CRD) experiment with three replications was conducted to assess the impact of AsA on wheat under drought stress (50% field capacity). Wheat plants were sprayed with three different concentrations of AsA (200 µM, 400 µM, and 600 µM), and their physiological and growth responses were analyzed using various methodologies, including spectrometry, the digestion method, flame photometry, microscopy, moisture content measurement, and field capacity assessment. The data were statistically evaluated using the Statistix-8.1 software. Results demonstrated that drought stress significantly reduced growth parameters and ion concentrations while increasing hydrogen peroxide levels compared to the control. However, AsA application improved plant resilience, enhancing growth metrics, soluble sugar, flavonoids, anthocyanin, ascorbic acid content, chlorophyll, and ion concentrations under drought conditions. The 600 µM AsA concentration had the most pronounced positive effects on all tested variables. These findings suggest that AsA can serve as a potential growth promoter, alleviating drought-induced damage and optimizing the morpho-physiological and biochemical attributes of wheat.